Excretion of citalopram in breast milk - Spigset, Olav (1997)
Aims The objective of this study was to measure the secretion of the selective serotonin uptake inhibitor citalopram in breast milk. Methods The excretion of citalopram in breast milk was studied at steady-state conditions in two patients with depression and in one healthy volunteer after ingestion of a single dose citalopram. Results Milk/serum concentration ratios based on single pairs of samples from the two patients ranged from 1.16 to 1.88. Based on milk concentration data from the patients, the absolute dose ingested by a suckling infant would be 4.3–17.6 μg kg(−1) day(−1), and the relative dose 0.7–5.9% of the weight-adjusted maternal dose. Based on area-under-the-time-concentration curves from the healthy volunteer, the milk/serum ratio was 1.00, the absolute dose to the infant during steady-state conditions would be 11.2 μg kg(−1) day(−1) and the relative dose 1.8% of the weight-adjusted maternal dose. Conclusion The study shows that the relative dose to a suckling infant is close to that reported for fluoxetine, and higher than reported for fluvoxamine, paroxetine and sertraline.